Planning of a Charging Station for Electric and Hydrogen Vehicles Under Hydrogen Storage and Fuel Cell Systems Using a Novel Stochastic P-Robust Optimization Technique - Sabzalian , M (Elsevier Ltd, 2024)
This article presented a robust plan for an off-grid charging station (OGCS) for electric vehicles (EVs) and hydrogen vehicles (HVs) based on a photovoltaic (PV) system and a hydrogen storage system (HSS). This OGCS simultaneously supplies HVs and EVs continuously throughout the day. Also, HSS and fuel cell (FC) systems have been allocated in the OGCS to be used when we do not have access to the power of the PV system. In addition, a diesel generator (DG) is also designed to prevent in cases where we have extreme uncertainty, including the lack of energy in the PV system and the high load of the system, which may lead to load interruption. Uncertainties of electric and hydrogen loads of EVs and HVs in addition to PV production power are simulated using scenario-based stochastic optimization technique (SOT). Finally, a new framework based on stochastic p-robust optimization technique (SPROT) is applied to optimize the maximum relative regret (MRR) in the worst scenario in order to achieve robust planning in the uncertain environment. The obtained results from the proposed SPROT are compared with SOT. The compared results indicate a 4.51% raise in the average cost in SPROT and a 45.73% decrease in MRR that leads to robust planning. Finally, installed capacity of PV system will decrease from 1688 to 1685 kW, while installed capacity of DG will increase from 78 to 123 kW. © 2024 Hydrogen Energy Publications LLC